To study outcome of surgical management of distal 3rd and proximal 3rd fractures of tibia in adults using expert tibial nails - Kachhap, N. D.; Kumar, Amit; Kumar, M. M.; Kumar, Devendra; Kumar, Birendra; Kumar, Deepak (International Journal of Research in Orthopaedics, 2017)
Background: Tibia is most commonly fractured long bone. Within few years population of India and number of vehicles has increased very much. This has lead to manifold increase in not only rate of tibia fracture but also in complexity of fracture. Using interlocking nail in tibial fracture with short proximal and distal fragment render it unstable leading to frequent loss of reduction causing malunion. Multidirectional interlocking screws ensure that alignment can be well maintained and stability preserved in short proximal or distal tibial segments. Methods: A prospective, non randomized study was conducted comprising of 30 patients of proximal and distal 1/3rd fracture of tibia in, Department of Orthopaedics, Bokaro General Hospital. The method used for fracture fixation was open/closed reduction and internal fixation with expert tibial nail. The duration of study was June 2013 to June 2016. The data thus obtained was evaluated in terms of mode of injury, associated injury, fracture pattern, etc. Also outcome was measured and complication were evaluated and treated. Functional outcome was evaluated using hospital for special surgery (HSS) knee score. Results: All 30 patient were followed up successfully during period of 3 years. The mean duration of radiological union in this study was 20.6 weeks, though it ranged from 18 to 26 weeks. 8 patients developed some complication in form of superficial infection, malunion etc but none of the patient had non-union of fractured bone. On the basis of hospital for special surgery (HSS) knee score13 patients had excellent results; 9 had good results, 05 had fair results and 3 had poor result. Mean HSS knee score was 82.3 (SD 15.3) after 3 years of follow up. Conclusions: Expert tibial interlocking nail is good treatment option for distal and proximal 1/3 fracture of tibia especially in non intra-articular facture. It can be used in simple intra-articular fracture but additional hardware is required.